Total Hip Arthroplasty in a Case of Neglected Central Hip Dislocation with Isolated Quadrilateral Plate Fracture: A Case Report with Review of Literature - Somok Banerjee; Santu Sarkar; Alok Chandra Agrawal; Harshal Sakale; Suhas Mahendrakar; Devashish Singh (Journal of Orthopaedic Case Reports)
Introduction: Isolated quadrilateral plate fracture with central hip dislocation is a rare occurrence. Such difficult-to-treat fractures can be managed with both open reduction and internal fixation (ORIF) and total hip arthroplasty (THA). We hereby describe the management of such a case of neglected irreducible central hip dislocation with quadrilateral plate fracture with THA in this case report. Case Report: A 55-year-old male patient presented to our outpatient department with 5 month old neglected post-traumatic central dislocation of the hip with a quadrilateral plate fracture. Initially, ORIF with infrapectineal plating was planned by anterior intra-pelvic approach. But despite best efforts (lateral and longitudinal traction along with reduction tools and maneuvers) it was not possible to reduce the head femur back into the native acetabular floor due to the long-standing napkin ring constriction. It was decided intra-operatively to proceed with THA. The patient was subsequently repositioned for THA using a standard posterior approach. The head femur was removed piecemeal and the medial wall defect was reconstructed using contoured titanium mesh with impaction bone grafting and rest THA was done in the usual manner. The patient was mobilized from 2nd post-operative day and allowed partial weight bearing with gradual progression to full weight bearing by 3rd week. He could return to his daily activities by 6 months and had a Modified Harris Hip Score of 91 in 1 year follow-up. Radiographs revealed well incorporation of the bone graft with no evidence of loosening. The patient didn’t have any complications such as infection. Heterotopic ossification or dislocation. Conclusion: THA in neglected irreducible central hip dislocation with quadrilateral plate fracture has good functional and radiological outcome.